The Paradox of Legalization of Marriage (Itsbat Nikah) in The Paradox Indonesia: Legal Protection or Loophole - Zaitun Abdullah; Putri Ayu Maharani (Sociological Jurisprudence Journal, 2025)
This study aims to criticize the effectiveness of the legalization of marriage (itsbat nikah) procedure in Indonesia as a legal mechanism to validate unregistered marriages (nikah siri), using the analytical tools of eclecticism and maslahah theory. The legalization of marriage procedure is intended to protect the rights of couples and children when the marriage has not been officially registered. However, the number of legalizing marriage applications continues to increase every year, indicating that unregistered marriages are still rampant in Indonesia. This trend raises concerns about whether the itsbat nikah procedure effectively enforces the law or provide a way to avoid the requirements of a valid marriage. Using normative legal research methods, this study analyzes relevant court decisions, statistical data from supreme courts, and interviews with legal practitioners involved in the implementation of itsbat nikah. The findings of this study reveal that although itsbat nikah provides a legal solution for those who are in a religiously valid but unregistered. It also risks public legal awareness by being considered an easy solution, if there are marriages that still do not fulfil the requirements of marriage to carry out a nikah siri first. Referring to the theory of legal eclecticism, this study highlights the problems between religious practices, state law, and broader implications for legal education and social responsibility in marriage registration. Sharia provisions regarding Itsbat nikah should aim to uphold justice and the welfare of society, including ensuring legal recognition and protection of the rights of the parties involved in a marriage.